The influence of tobacco smoking on physical activity and length and quality of sleep among medical students. A preliminary study - Torres, Kamil; Staśkiewicz, Grzegorz; Pietrzyk, Łukasz; Lisiecka, Justyna; Torres, Anna; Maciejewski, Ryszard (Polish Journal of Public Health, 2012)
Introduction. Smoking brings about negative consequences such as addiction and disturbance of the natural homeostasis of organism. Physical activity and the amount of sleep also seem to be vital as far as the health is concerned. Aim. Evaluation of the influence of smoking habit on physical activity, length and quality of sleep among medicine students and confirmation if the origin takes part in this correlation. Material and methods. An anonymous questionnaire was distributed to 134 Polish (P group), American (A group) and Norwegian (N group) students of the Medical University of Lublin. Students were asked about their sport preferences, smoking habits, sleeping and studying habits. To assess differences between the three study groups the Kruskal-Wallis test, Mann-Whitney U-test and Chi-square test were used. Results. The majority of students from the P, A and N groups do not smoke. Among the P group, nonsmokers made up 90%, among A group, 88% and in the N group, 80%. All three groups of medical students claim that smoking negatively influences physical condition. In group P, 10% of students reported sleep-related problems, while in groups A and N, 30.4% and 24%, respectively. All of the smokers think that their sleep duration is not long enough in comparison to the nonsmokers. Conclusions. All three ethnic groups of medical students demonstrated an overall positive attitude towards living a healthy lifestyle, however significant differences were observed between the groups of different origins. The results indicated that smoking strongly influences different habits.